Museum Bali Sebagai Sarana Pendidikan, Media Pembelajaran, dan Pelestarian Sejarah Lokal Masyarakat Bali - Ahmad Nasir (Historia Pedagogia, 2026)
This study aims to examine and describe the role of the Bali Museum in supporting and complementing the implementation of the history education curriculum in schools, analyze and assess the use of museum collections as a history learning medium for students, and identify various strategies implemented by the museum in its efforts to preserve and instill local historical values. The research method used was descriptive qualitative research through a survey using the Miles and Huberman data analysis technique. The results demonstrate the role and contribution of the Bali Museum in supporting and complementing the implementation of history education. The identified strategies employed by the management in preserving, promoting, and instilling local historical values ​​include the Bali Museum's Living Museum concept, the use of lontar as a historical and cultural resource, and the Tri Hita Karana concept as a Balinese philosophy of life. This indicates that the Bali Museum functions not only as a place to store collections but also as a center for history education based on local wisdom.